(untitled) (Annals of Medical Research, 2023)
Aim: Evaluate the impact of Tenofovir Disoproxil Fumarate (TDF) treatment on bone mineral density (BMD) for patients with chronic hepatitis B (CHB) with Dual X-ray absorptiometry (DEXA) and the Fracture Risk Assessment Tool (FRAX) score. Materials and Methods: A total of 38 CHB patients treated with TDF were included in this retrospective study. To estimate BMD, DEXA, demographic details, and laboratory values were examined in patients. The BMD measurements were compared after dividing the patients into 3 groups as normal BMD, osteopenic, and osteoporotic. FRAX scores (before and after DEXA) were calculated. Results: Twenty-one of the 38 (55.3%) cases of CHB infection were male, the median age was 51 (min-max: 29-71) years, and seven patients (18.4%) were over 60 years of age. The median TDF duration was median 6 (min-max: 3-13) years. Osteopenia, defined by DEXA results, was found in 17 patients (44.7%) at the lumbar spine site, 11 (28.9%) at the femoral neck, and 10 (26.3%) at the total hip. Osteoporosis was detected in six patients (15.8%) at the lumbar spine site. Pre-DEXA FRAX score and post-DEXA FRAX score were calculated. Only one patient (1/33, 3%) had a score over the intervention threshold, by post-DEXA FRAX score. None of the patients classified as low risk based on the pre-DEXA FRAX score had a post-DEXA FRAX score above the intervention threshold. When the TDF duration, serum phosphorus level, vitamin D levels, and ALP levels were compared, no significant differences were found between the groups. Conclusion: There are concerns about the negative effects of TDF used in CHB infection on BMD. However, BMD loss may not increase as the duration of TDF use increases. FRAX score is useful in identifying to risk of osteoporotic fracture. FRAX score can also eliminate the need for DEXA in most CHB cases. The FRAX score should be used in clinical practice to determine cases at risk.